Scientific-Theoretical and Practical Directions of Uzbek Folklore of the Twentieth Century - Sultanovich, Amonov Ulugmurod (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the scientific, theoretical and practical development of Uzbek folk poetry and folklore , which was formed as a science in the early twentieth century . In this work , the development of Uzbek folklore in the early twentieth century is considered to be two stages, first in the practical, then in the scientific-theoretical stage, and then this scientific opinion is based on the following. At the practical stage, work was carried out to identify and record people who knew and were able to perform folklore, to prepare and publish recorded folklore works, and at the scientific - theoretical stage , to seriously study the published folklore works. It is proved on the basis of scientific sources and publications that the work on giving theoretical conclusions about their genre nature and poetic features was started.